Livestock feed resources used as alternatives during feed shortages and their impact on the environment and ruminant performance in West Africa: a systematic review - Alimi, Nouroudine; Assani, Alassan S.; Sanni Worogo, Hilaire; Baco, Nasser Mohamed; Traoré, Ibrahim Alkoiret (Frontiers in Veterinary Science, 2024)
Ruminant feed is a major problem for livestock sector in West-Africa developing countries by causing animal nutritionnal diseases, drive down ruminants production and creating a massive ecological crisis by greenhouse gas emissions. Alternative feeds, which include agro-industrial by-products, fodder trees, crop residues, insects , fodder legumes, algae and pulses, constitute enormous feed resources for livestock in Africa. This study was conducted in accordance with the methodological recommendations of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). We perfomed literature search using Google Scholar, Web of Science and Scopus to identify documents dealing with ruminant alternative feeds by using these key words: alternative feeds, ruminants' products, environmental impacts and West-Africa. Those that met the inclusion criteria were taken into account, resulting in 44 articles published between 2013 and 2023. These studies involved 45 alternative feeds divided into six (6) groups, including agro-industrial by-products (48.89%), followed by fodder trees (17.78%), crop residues (13.33%), insects (8.89%), fodder legumes (6.67%) and seaweeds (4.44%). Our results revealed that alternative feeds ressources and their effects on ruminants and environmental performances in West-Africa are poorly known, limiting their incorporation in rations and sometimes leading to their misuse. Future research should focus on these aspects in order to make efficient use of these resources to improve ruminant milk and meat production.